Developmental mechanisms channeling cortical evolution. Issue 2 (February 2015) - Finlay, Barbara L.; Uchiyama, Ryutaro
Highlights Across species, disparity in neuron number per column grows with cortical size. A rostrocaudal gradient in neurogenesis duration generates this disparity in neuron number. Anisotropies in early axon extension further organize cortical area hierarchy. We suggest that the cortex has two zones of contrasting intrinsic topology. These mechanisms may progressively amplify hierarchical processing in larger brains.